PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP RETURN SAHAM STUDI PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2019-2022 - Santia, Tia Pebrianti; Hidayati, Siti Aisyah (Jurnal Magister Manajemen, 2024)
The purpose of this study was to examine the effect of Capital Structure and Profitability on Stock Returns in food and beverage companies listed on the Indonesia Stock Exchange in 2019 2022.This type of associative research with a quantitative approach. Samples were taken using purposive sampling technique. In this study, the sample consisted of 27 companies from 30 food and beverage companies listed on the Indonesia Stock Exchange in 2019-2022, so the research data analyzed amounted to 108 observations. The panel data analysis method in this research is multiple linear regression analysis using Eviews version 12. The results of this research show that the Debt to Equity Ratio has a positive but significant effect on stock returns. Meanwhile, Return On Asset shows that it has a positive and insignificant effect on stock returns. For further research, it is hoped that researchers can expand the scope of research objects to the company sectors on the Indonesian Stock Exchange so that they can add more diverse research variables.